Chemical Composition of Leaves of Chinese Quince (Pseudocydonia sinensis (Thouin) C.K. Schneid.) - Grygorieva, Olga; Klymenko, Svitlana; Vergun, Olena; Shelepova, Olga; Vinogradova, Yulia; Ilinska, Antonina; Horčinová Sedláčková, Vladimíra; Brindza, Jan (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2020)
Pseudocydonia sinensis (Thouin) C.K. Schneid. less known plant species in the Ukraine conditions, but the fruits were widely used in traditional Chinese medicine for the treatment of asthma, colds, sore throat, mastitis, rheumatoid arthritis, and tuberculosis. In this study, chemical compositions of the leaves of Pseudocydonia sinensis were investigated. They contained total protein 6.66 %, ash 8.54 %, lipids 3.38 %, beta carotene 90.30 mg/kg DW. Monosaccharide analysis revealed that the neutral carbohydrate part (fructose, maltose, sucrose, and lactose) was found in low amounts only (< 0.5 g/kg). The major quantitative tocopherol in leaves was α-tocopherol (80.73 mg/kg DW). Saturated, monounsaturated and polyunsaturated fatty acids, palmitic acid (C16:0; 53.36 g/100 g DW), oleic acid (C18:1; 12.49 g/100 g DW) and linoleic acid (C18:2; 8.24 g/100 g DW), respectively, were found predominant. Palmitic acid makes up 57.2 % of the total amount. The total amount of amino acids found in the leaves was 53.90 g/kg DW, including total essential amino acids (28.60 g/kg DW) and percentage of total essential amino acids (53.06 %). Glutamic acid was found of leaves to be the dominant free amino acid (6.5 g/kg DW) followed by aspartic acid (5.4 g/kg DW) and leucine (4.9 g/kg DW DW). The mineral composition of leaves of P. sinensis demonstrated the presence of elements in following order: Ca>K>Mg>P>S>Fe>Zn>Na>Mn>Al>Cu>Ni>Cr>Pb>Cd>Hg>As>Se. Studied antioxidant parameters showed that antioxidant activity by DPPH and molybdenum reducing power was 8.76 and 289.73 mg TE/g, respectively. Also, the total content of polyphenols, flavonoids, and phenolic acids amounted to 65.77 mg GAE/g, 22.47 mg QE/g, and 9.06 mg CAE/g, respectively. The obtained data represent that leaves of P. sisnensis contain rich mineral composition, amino, and fatty acid composition and biologically active compounds such as polyphenols that can be used in the pharmaceutical study to validate its possible medicinal application. The study of less know and neglected plant species and it’s raw can increase possible use in human life beneficial plant products.